1999
DOI: 10.2535/ofaj1936.75.6_305
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Study of Complex Anomalies of the Digastric Muscle and Review of the Literature

Abstract: Summary: The digastric muscles of 99 cadavers were examined bilaterally. In 5 of them, the digastric muscles showed different types of complex abnormalities.These complex anomalies should be kept in mind in functional studies involving the floor of mouth and evaluating the same structures with CT and MR imaging. Secondly, the embryological basis of the isolated anomalies of the anterior digastric muscle with respect to its occurrence together with the mylohyoid muscle stressed in this article needs further stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 10 publications
2
32
0
Order By: Relevance
“…These muscle bundles were attached to the intermediate tendon and continued with the posterior belly. As well, Aktekin et al 16 described a rare event bilateral and symmetrical variation of the anterior belly of the digastric muscle in the form of cruz. Others authors report the presence of a previous bilateral accessory belly originating in the intermediate tendon and inserted in mylohyoidraphe.…”
Section: Resultsmentioning
confidence: 94%
“…These muscle bundles were attached to the intermediate tendon and continued with the posterior belly. As well, Aktekin et al 16 described a rare event bilateral and symmetrical variation of the anterior belly of the digastric muscle in the form of cruz. Others authors report the presence of a previous bilateral accessory belly originating in the intermediate tendon and inserted in mylohyoidraphe.…”
Section: Resultsmentioning
confidence: 94%
“…The abnormalities are more often unilateral and mostly related to the anterior belly of digastric muscle [2,3]. However, the anatomical literature yields little information about the variations of the PBDM.…”
Section: Discussionmentioning
confidence: 97%
“…Several anatomical and radiological studies have demonstrated the existence of anomalies of the digastric muscle [2,3]. Although abnormalities of the anterior belly have commonly been noted in previous studies, the anatomical literature does not provide adequate data about variations of the PBDM.…”
Section: Introductionmentioning
confidence: 94%
“…22 Anterior digastric variants have been documented to occur unilaterally, bilaterally, symmetrically, and asymmetrically and insert both ipsilateral and contralateral to the origin of the muscle. 23,24 Variant anterior bellies have been reported to occur at a frequency ranging from 2.7% to 69.6%, respectively. 25,26 …”
Section: Variant Anterior Digastric Musculaturementioning
confidence: 99%
“…Many variants meeting these criteria have been described, including additional muscle bellies spanning from the digastric fossa to the ipsilateral intermediate tendon/hyoid and additional muscle bellies spanning from the digastric fossa to the contralateral tendon/hyoid. 23,24 Anterior belly of digastric muscle variants have been identified via computed tomography and magnetic resonance imaging 25,28 ; therefore, screening for adequate variant musculature may be accomplished with advanced imaging techniques. Screening the submental region is also important in differentiating variant anterior digastric anatomy from submental lymph nodes, space occupying lesions, and muscular asymmetries due to trigeminal nerve lesion.…”
Section: Evaluation Of the Hypothesismentioning
confidence: 99%